The Role of Civic Education in the Integration of the Indonesian Nation - Fortuna, Refni; Khadir, Abdul (Jurnal Pendidikan Amartha, 2022)
Civic education is an important teaching that should be introduced to children as early as possible. This education is closely related to a person's character and character. The purpose of this education is to become a society that has high moral values and is virtuous like the values that have been contained in Pancasila. One of the values already contained in it is the state's goal to always integrate without any divisions in it. There needs to be character building education for children and the Indonesian people starting from the family scope. Today, character education is very much needed and is considered to be able to make every human being smart, virtuous and behave politely. Moral and virtuous character education is embodied in civics education (PKn) subjects which are carried out at every school level. Based on the results and discussion, it can be understood that the role of civic education is to foster citizens, especially the next generation who are good for the life of the nation and state. Citizenship education for the next generation is very important in order to raise awareness of defending the country and increasing love for the homeland.